Post-harvest Management of Alternaria Induced Rot in Tomato Fruits With Essential Oil of Zanthoxylum armatum DC - Slathia, Shummu; Sharma, Yash Pal; Hakla, Haroon Rashid; Urfan, Mohammad; Yadav, Narendra Singh; Pal, Sikander (Frontiers in Sustainable Food Systems, 2021)
Alternaria fruit rot is a major disease caused by Alternaria alternata (Fr.) Keissl. a prolific fungal pathogen. Among postharvest diseases of tomato, fruit rot induced by A. alternata is the most damaging. Antifungal agents are widely used to control postharvest management of tomato fruits. However; negative impacts of fungicidal residues in edible fruits and vegetables on human health cannot be over ruled. Eco-friendly ways of controlling Alternaria rot in tomato fruits offers a novel way of tomato rot management. Current study proposes an alternate method in controlling tomato fruit rots through Zanthoxylum armatum DC essential oil (EO) application. Gas chromatography-mass spectrometry profiling showed eucalyptol and sabinene as major components of Z. armatum EO. Furthermore, EO applied (0.5 to 6 µL/mL) showed significant inhibition of A. alternata growth (p > 0.05) at 6 µl concentration tested. Lipid peroxidation assays revealed significant reduction in membrane damage in tomato fruits treated by EO compared to alone inoculated fruits with A. alternata. Elevated activities of superoxide dismutase, catalase, ascorbate peroxidase and glutathione reductase coupled with enhanced antioxidants such as ascorbic acid, glutathione, proline and total phenols in EO treated fruits may be linked with better fruit rot management than control fruits inoculated with A. alternata induced rot alone. Mycelia and spore production was dramatically reduced in EO applied tomato fruits over A. alternata alone in tomato fruits (p > 0.05). Interestingly, free radical scavenging activities of EO applied tomato fruits showed significant improvement compared to only pathogen inoculated tomato fruits. Findings propose practical utility of Z. armatum EO as a plant-based antifungal for post harvest management of Alternaria rot in tomato fruits.